2019
DOI: 10.1038/s41538-019-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-capped gold nanoparticles for indicating temperature abuse in frozen stored products

Abstract: The present study aimed to optimize the conditions for the synthesis of gold nanoparticles (AuNP) using chitosan and to assess its effectiveness as temperature threshold indication for frozen storage conditions. Chitosan concentration of 0.25% and temperature of 90 °C for 15 min was optimum for synthesizing AuNP. The maximum absorbance ( λ max ) was observed at 530 and 540 nm for 0.125% and 0.25% chitosan, respectively, indicating shifting of peak toward longer wavelengths (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 22 publications
4
52
0
Order By: Relevance
“…The high thermostability of Chlorella vulgaris soluble polysaccharides may be due to the presence of uronic acids and sulfate groups that disallowed full polymer degradation. In addition, the thermogram is consistent with the hydrophilic nature of the polysaccharides functional groups 54,71 . The present thermogravimetric profile (TGA) data are in agreement with the thermal behavior of the soluble polysaccharide (ulvan) produced by Ulva lactuca and Ulva fasciata as demonstrated by Hussein et al 69 .…”
Section: Antioxidant Activity Of Chlorella Vulgaris Extracted Polysacsupporting
confidence: 70%
See 1 more Smart Citation
“…The high thermostability of Chlorella vulgaris soluble polysaccharides may be due to the presence of uronic acids and sulfate groups that disallowed full polymer degradation. In addition, the thermogram is consistent with the hydrophilic nature of the polysaccharides functional groups 54,71 . The present thermogravimetric profile (TGA) data are in agreement with the thermal behavior of the soluble polysaccharide (ulvan) produced by Ulva lactuca and Ulva fasciata as demonstrated by Hussein et al 69 .…”
Section: Antioxidant Activity Of Chlorella Vulgaris Extracted Polysacsupporting
confidence: 70%
“…The peak at 2927 cm −1 corresponds to CH 2 asymmetric stretching vibration 53 . The peak observed at 2856 cm −1 is attributed to C-H groups 54 , the peak spectrum at 2856 cm −1 corresponds to stretching of C-H, -CH 3 , and >CH 2 functional groups 55 . Kamnev et al 52 demonstrated that, the band at 1730 cm −1 is related to the C=O stretching of aldehydes, ketones, carboxylic acids and esters.…”
Section: Uv Characterization Of Extracted Chlorella Vulgaris Soluble mentioning
confidence: 99%
“…Fourier-transform infrared (FTIR) spectra revealed that blankgel and L-AgÅPs-gel displayed the same peak shape, position (3357 and 1639 cm −1 ), and intensity of absorbance bands attributed to the NH stretching vibrations and the vibrations of carbonyl bonds (C═O) (18), respectively ( Fig. 1I), suggesting that the incorporation of L-AgÅPs does not cause any structural changes of carbomer gel.…”
Section: Characterization Of L-agåps and L-agåps-gelmentioning
confidence: 92%
“…Au nanoparticles transform its color and intensity with variation in storage temperature and its duration. This difference in color and intensity is principally owing to the change in shape and size of chitosan capped Au nanoparticles, potentially used for the development of sensors in food [ 49 ].…”
Section: Introductionmentioning
confidence: 99%